Ice accretion on aerofoils - Janjua, Zaid Ayaz (2017)
Ice accretion on aerofoils is a problematic phenomenon affecting power lines, ships and aircraft wings. This work thus undertakes an experimental and computational investigation into the formation and adhesion of ice on aerofoils. An experimental setup to test the adhesion strength of ice was designed and tested for repeatability and the effect of temperature on it. It was found that the ambient temperature has a profound effect on the adhesion strength, possibly due to dependence on the heat transfer mechanism through an amorphous liquid-like layer between ice and substrate. The tests were expanded to determine the effect of contact angle parameters on the icephobicity of 14 nanocoatings. It was found that the surface should possess high receding contact angle and low CAH to reduce adhesion thereby reducing the ice-substrate contact points. Hydrophobicity and icephobicity may not necessarily be dual characteristics of a surface unless the aforementioned criteria is satisfied. Anti-icing tests on the same coatings showed that the freezing time of a droplet on the surface reduces with an increase in static contact angle. To understand the role of mixed ice, a one dimensional model is introduced to measure the accretion of mixed, rime and glaze ice on an aerofoil. This process occurs in four distinct stages and the effect of atmospheric parameters on the transition time between different growth types and height is determined. This mode was developed further to include a convective term to determine the profile of ice when rime grows above glaze/mixed with water flowing inside. This is a first step towards understanding the links between porous structures, ice structures and runback water that can generate interesting icy structures. This work forms part of the ICECOAT project funded by the EU Framework 7 CleanSky programme under grant award JTI-CS-2012-02-SFWA-01-051.